Cover Image, Volume 119, Number 5, May 2022. Issue 5 (12th April 2022) - Belliveau, Jessica; Papoutsakis, Eleftherios T.
Abstract : The cover image is based on the Article Extracellular vesicles facilitate large‐scale dynamic exchange of proteins and RNA among cultured Chinese hamster ovary and human cells by Jessica Belliveau and Eleftherios T. Papoutsakis., https://doi.org/10.1002/bit.28053 .